Vasitis nodosa and associated clinical findings. Issue 4 (April 1988) - Hirschowitz, L; Rode, J; Guillebaud, J; Bounds, W; Moss, E
Abstract : To establish the prevalence of vasitis nodosa in patients who had undergone vasectomy segments of vas deferens resected from 40 patients at the time of vasectomy reversal were examined histologically and immunohistochemically. The findings were correlated with clinical history and postoperative outcome. Controls comprised segments of normal vas deferens excised at vasectomy. Twenty of the 40 vasovasostomy specimens showed vasitis nodosa; in 13 this was associated with sperm granulomas and in two with spermatocoeles. The vasitis nodosa was characterised by multiple small ductules extending from the central lumen of the vas into the muscle layers and adventitia. In 14 cases there was mucinous metaplasia of the epithelium lining the ductules. The number of nerve fibres in the submucosa and muscle layers was reduced after vasectomy. In patients with vasitis, however, hyperplasia of nerve fibres in the adventitia (16 of 20 cases) and formation of neuromas were seen. Nerve fibre hyperplasia was seen in only one, and sperm granulomas and spermatocoeles in none of the 20 specimens without vasitis nodosa. The development of vasitis nodosa was independent of the patients' age or the interval between vasectomy and reversal. The restoration of fertility did not seem to be affected by previous vasitis nodosa.